Microsatellite DNA polymorphism of the Long Horned Ankole cattle in Uganda - Kugonza, Donald R.; Han Jianlin; Okeyo Mwai, Ally; Kiwuwa, G.H.; Hanotte, Olivier H. (TSAP and ILRI, 2006)
Nineteen microsatellite markers were used to investigate the genetic diversity, phylogenetic relationships and herd structure of Ugandan Ankole cattle. A total of 304 animals from 8 herds in Mbarara District were characterised. Across all loci, 200 alleles were observed. A high mean number of alleles (MNA) per locus, ranging from 5.89 to 6.79 per herd, was observed. Polymorphic information content (PIC) ranged from 0.403 (ILSTS013) to 0.817 (ILSTS036), with an overall mean of 0.688. The average observed heterozygosity (Ho) was highest in Kaibanda (0.727) and lowest in Kituuha (0.648), while the expected heterozygosity (He) ranged from 0.722 (Nshaara) to 0.664 (Kituuha). Significant deviations from Hardy-Weinberg proportions were observed on 8 loci, however, all 152 loci-herd combination tests were in equilibrium after Bonferroni correction. FST estimates for all loci and between all herds were highly significant (P<0.001), suggesting little if any gene flow between the herds. For all herd pairs, FST values were generally low, with an overall mean of 0.041 + 0.08. Significant (P<0.01) inbreeding effect (FIS) was detected in the Nasasira herd. The mean number of migrants per generation (Nm) across all herds was 3.82. Phylogenetic analysis showed that herds from the same geographical counties grouped together. These results illustrate at the molecular level the fairly wide genetic variation found among the Ankole herds studied and therefore the potential for genetic improvement of these herds.